2017
DOI: 10.1111/cei.12918
|View full text |Cite
|
Sign up to set email alerts
|

High endothelial venules associated with T cell subsets in the inflamed gut of newly diagnosed inflammatory bowel disease patients

Abstract: Naive and central memory T lymphocytes (T and T ) can infiltrate the inflamed gut mucosa in inflammatory bowel disease (IBD) patients. Homing of these subsets to the gut might be explained by ectopic formation of tertiary lymphoid organs (TLOs), containing high endothelial venules (HEVs). We aimed to evaluate the presence of HEVs and TLOs in inflamed intestinal mucosa of newly diagnosed, untreated IBD patients in relation to the presence of T and T lymphocytes. IBD patients (n = 39) and healthy controls (n = 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 35 publications
1
23
1
Order By: Relevance
“…Our findings of PNAd + venules being present in the colonic mucosa during inflammation of UC are in line with two earlier studies performed in a small patient group [14,15]. However, these studies did not take MAdCAM-1 positivity into account, and were cross-sectional in design providing no information during the follow-up of the disease.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings of PNAd + venules being present in the colonic mucosa during inflammation of UC are in line with two earlier studies performed in a small patient group [14,15]. However, these studies did not take MAdCAM-1 positivity into account, and were cross-sectional in design providing no information during the follow-up of the disease.…”
Section: Discussionsupporting
confidence: 91%
“…Results from the previous studies using different methods (flowcytometry versus immunohistochemistry) suggest the recruitment of L-selectin-expressing naive T cells through these PNAd + HEVs [14,15]. Categorizing patients into groups based on the relative number of PNAd + venules (HEV high and HEV low ), a correlation was found between the presence of more lymphoid follicles and higher percentages of Tn and Tcm lymphocytes in the HEV high group [14]. In the present study, we demonstrated a statistically significant correlation between the proportion of PNAd + venules and the number of lymphoid follicles.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…34 Lymphoid follicles were also associated with high endothelial venules, facilitating homing of immune cells. 35…”
Section: Discussionmentioning
confidence: 99%